Getting it right : a handbook for successful school leadership - Jenkins, H. O. (Oxford : Basil Blackwell, 1991)
Suggests a number of key management prescriptions considered essential for successful school leadership, recommending that the effective school leader should inspire a clear vision, empower staff, create fair systems, give instructional leadership, take risks and respect the customer.
Keywords: School management and organization -- Great Britain; School management and organization; Great Britain; Schools -- Management; Great Britain